Body image and nonsuicidal self‐injury: Validation of the Body Investment Scale in participants with eating disorders. (18th September 2017) - Marco, J. H.; Cañabate, M.; García‐Alandete, J.; Llorca, G.; Real‐López, M.; Beltrán, M.; Pérez, S.
Abstract : The Body Investment Scale (BIS) assesses body image feelings, body care, protection of the body, and comfort in touch, in order to identify and distinguish participants with self‐harming and self‐destructive tendencies. However, the psychometric properties of the BIS were not analysed in participants diagnosed with eating disorders. The main objective of the present study is to confirm the factor structure of the Spanish version of the BIS and analyse its psychometric properties in a sample composed of women diagnosed with eating disorders. Participants were 250 Spanish women between 12 and 60 years old ( M  = 26.05, SD  = 11.97) diagnosed with eating disorders. A confirmatory factor analysis showed a poor fit of the original BIS. The final model showed an acceptable 4‐factor structure (Body Feelings, α = .88; Body Touch, α = .82; Body Protection, α = .77; Body Care, α = .68), with a good fit to the data (SBχ 2 (246)  = 393.21, CFI = .906, IFI = .908, RMSEA = .049). The relationships between the BIS and both the Purpose‐In‐Life Test—10 Items and Beck Hopelessness Scale were analysed, as well as differences in the BIS score according to nonsuicidal self‐injuries and suicidal ideation in the past year. The BIS is an appropriate instrument to assess the body investment dimension of body image in women with eating disorders.